Acting Out Strategy In Parepare Students Class XI MIA 2 MAN 2 Parepare - Muh. Siri Dangnga; Sukeriyadi, Mutmainnah; Ahdar (IAIN Parepare, 2022)
This thesis discusses the strategy of Acting out in the Akidah Akhlak subject in familiarizing the polite attitude of students in class XI MIA 2 MAN 2 Parepare. This research is a descriptive qualitative research. This study research was conducted to find out the strategies of Akidah Akhlak subject teachers in getting used to the polite attitude of students and the supporting and inhibiting factors of Akidah Akhlak subject teachers in getting used to the polite attitude of students. In this study, the data collection methods used were observation, interviews, and documentation with data processing steps, namely data collection, data reduction, data presentation and drawing conclusions. The credibility test was carried out using the data triangulation method. Based on the results of the study, it was found that the Acting out strategy in the Akidah Akhlak subject carried out by the teacher in familiarizing students with polite attitudes was quite effective in the aspects of religious and moral values of class XI MIA 2 students. In this case, the teacher provided motivation and advice to familiarize manners in everyday life such as in dressing, decorating, traveling. The supporting factors in getting used to polite behavior using the acting out strategy are the enthusiasm of students and facilities and infrastructure while the inhibiting factors are requiring a long time allocation and lack of preparation from each group. The researcher draws conclusions from all the data that has been obtained, namely that teachers of the Aqidah Akhlak subject by using the acting out strategy can familiarize students with polite attitudes. Therefore, the habituation of politeness can be applied by Akidah Akhlak teacher for all students at MAN 2 Parepare.